2022
DOI: 10.35772/ghm.2021.01077
|View full text |Cite
|
Sign up to set email alerts
|

The current status of robotic surgery for endometrial cancer in Japan

Abstract: The da Vinci ® surgical system (Intuitive Surgical Inc., Sunnyvale, CA, USA) was approved in 2009 by the Japanese Ministry of Health, Labor, and Welfare. In gynecology, robotic surgery for hysterectomy for benign indications and early-stage endometrial cancer has been covered by National Health Insurance since 2018. In a context where the da Vinci surgical system has prevailed in urology departments in Japan, gynecological robotic surgery has spread rapidly once it was covered by insurance. Although minimally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…It is argued that with an experienced and trained team, the effectiveness of robotic surgery will increase and eliminate complexity in difficult parts of the body [29,31]. There are studies showing that robot-assisted surgery is safe and effective in gynecological patients [29,32,33]. According to the patient results in our review, it appears that robotic surgery can also be used in gynecological patients.…”
Section: Effectiveness Of Robotic Surgery For Gynecological Patientsmentioning
confidence: 85%
See 2 more Smart Citations
“…It is argued that with an experienced and trained team, the effectiveness of robotic surgery will increase and eliminate complexity in difficult parts of the body [29,31]. There are studies showing that robot-assisted surgery is safe and effective in gynecological patients [29,32,33]. According to the patient results in our review, it appears that robotic surgery can also be used in gynecological patients.…”
Section: Effectiveness Of Robotic Surgery For Gynecological Patientsmentioning
confidence: 85%
“…No significant difference was found in studies comparing the duration of robotic surgery in obese and elderly patients [18,19]. It has been stated that the surgeon's experience and the training of the operating room staff will contribute to shortening the operating time [7,29,30]. In terms of nursing care, job descriptions in robotic surgery can be made and situations that prolong the operation time can be determined.…”
Section: Operative Timementioning
confidence: 99%
See 1 more Smart Citation
“…Endometrial cancer is a common gynecological cancer, and surgical treatments include hysterectomy, bilateral salpingo-oophorectomy, and lymph node (LN) dissection. With technological advancement in recent years, minimally invasive surgery (MIS), especially robotic surgery for endometrial cancer, has become mainstream; some reports have shown that it is more useful than conventional open or laparoscopic surgery [ 1 2 3 4 ]. In contrast, comprehensive lymphadenectomy is an essential procedure for endometrial cancer staging because lymph node metastasis (LNM) is an important poor prognostic factor.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, laparoscopic surgeries for gynecological malignancies increased by approximately 1.8-fold (from 1898 to 3490 cases) between 2014 and 2016 [16]. Robotic gynecological surgery has also rapidly increased in usage after being covered by the National Health Insurance in April 2018 [17]. However, these MIS procedures have been mainly employed in patients with endometrial cancer or benign conditions.…”
Section: Introductionmentioning
confidence: 99%